2009
DOI: 10.1371/journal.pone.0007109
|View full text |Cite
|
Sign up to set email alerts
|

Linking Chronic Infection and Autoimmune Diseases: Mycobacterium avium Subspecies paratuberculosis, SLC11A1 Polymorphisms and Type-1 Diabetes Mellitus

Abstract: BackgroundThe etiology of type 1 diabetes mellitus (T1DM) is still unknown; numerous studies are performed to unravel the environmental factors involved in triggering the disease. SLC11A1 is a membrane transporter that is expressed in late endosomes of antigen presenting cells involved in the immunopathogenic events leading to T1DM. Mycobacterium avium subsp. paratuberculosis (MAP) has been reported to be a possible trigger in the development of T1DM.Methodology/Principal FindingsFifty nine T1DM patients and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 36 publications
0
58
0
2
Order By: Relevance
“…However, Rani et al could not find any association despite the high prevalence of MAP and T1DM in India, probably due to the low number of patients investigated [21] or the genetic predisposition of the infected population in developing such an autoimmunity. Moreover, Paccagnini et al reported the association of the SLC11A1 gene in the Sardinian population either with T1DM or susceptibility to mycobacterial infection [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Rani et al could not find any association despite the high prevalence of MAP and T1DM in India, probably due to the low number of patients investigated [21] or the genetic predisposition of the infected population in developing such an autoimmunity. Moreover, Paccagnini et al reported the association of the SLC11A1 gene in the Sardinian population either with T1DM or susceptibility to mycobacterial infection [20].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MAP has been suggested as a possible cause of T1DM. The association of T1DM and MAP has been observed in the Sardinian population (Italy) [19,20], but a recent study could not replicate this finding in India, probably due to the small number of investigated samples [21].…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, a correlation between ELISA sero-positivity and SNP presence in 20% of the cases was observed. The association between rs2276631 SNP and Type 1 diabetes was recently reported [7], suggesting that the same polymorphism may be common to the major autoimmune diseases widespread in Sardinia.…”
Section: Figurementioning
confidence: 90%
“…Genomic DNA was purified from whole blood according to standard procedures [7]. Eight polymorphisms (rs2276631, rs3731865, rs3731864, rs17221959, rs2695342, rs2279015, rs17235409, rs17235416) were genotyped by PCR restriction fragment length polymorphism (RFLP) analysis, and the set of specific primers were designed based on the GenBank reference sequence (accession no.…”
Section: Snp Selection and Genotypingmentioning
confidence: 99%
“…Previous figures underestimated the scope of the problem, while even the most pessimistic predictions fell short of the current figure. It is predicted that the total number of people living with AD will increase drastically within the coming thirty years if no new and substantially more effective drugs are produced [4]. On 2009, estimated health costs of autoimmune disorders have exceeded 100 billion dollars only in the US.…”
Section: Introductionmentioning
confidence: 99%